Analisis Hubungan Otolith Terhadap Ukuran Ikan Dan Pengamatan Karakteristik Morfometrik Dan Meristik Ikan Kakap Genus Lutjanus - Suyatna, Muhammad Bagja Britania; Suyatna, Iwan; Pagoray, Henny; Fitriyana, Fitriyana; Syahrir, Muhammad (Sekolah Tinggi Pertanian Kutai Timur, 2023)
This study was performed in November 2021 to January 2022 at the Hydrooceanography laboratory, Faculty of Fisheries and Marine Science, University of Mulawarman, Samarinda, East Kalimantan. Fish samples of the study were collected from local fishers landed Fish Landing Ports (Pelabuhan Pendaratan Ikan, PPI) at Tanjung Limau Bontang and Toko Lima Muara Badak, Kutai Kartanegara, East Kalimantan. The aims of the study were to identify species of fish samples, to observe morphometric and meristic characters and to know the relationship between otolith sizes and fish sizes. The number of fish samples was 74 ind; all samples were measured and weighed; to know fish species of fish studied, identification was done on the basis of morphometric and meristic characters such as truss distance and fish length, hard and soft rays and specific signs found on the body was referring to research reports, related publication and fish identification manual. All fish otoliths were gathered from dissection of certain part of head, taken by forcep and measured by caliper, weigheg by digital scale, photograph with USB camera, fish distribution was known with calculating statistic descriptive,while the relationship between fish otolith size and fish size was analyzed using bivariate linear model. Results of laboratory observation, fish sample of the study consisted of Kakap Tompel Lutjanus russellii, Kakap Bakau L. argentimaculatus dan Kakap Merah L. gibbus; generally, fish sizes ranged from 34.68 – 2120.00 g; total length 12.20 - 51.20 cm, fish otolith weight 0.03 – 1.90 g; otolith lenght 0.47-1.96 cm; width 0.31-1.90 cm dan height of otolith 0.11-0.61 cm. After size of otoliths and the fish samples of the fish grouper were analyzed, the study showed that the otolith size followed the size of fish. Keywords : Pesisir, Bontang, Muara Badak, Selat Makassar, Model Linear Bivariate, Data, Correlation